Sublethal effects of copper nanoparticles on the histology of gill, liver and kidney of the Caspian roach, Rutilus rutilus caspicus - Sh. Aghamirkarimi; A. Mashinchian Moradi; I. Sharifpour; Sh. Jamili; P. Ghavam Mostafavi (Global Journal of Environmental Science and Management)
The current study has determined the toxicity effects of copper nanoparticles on the some vital organs such as gill, liver and kidney of Caspian Roach; Rutillus rutillus caspicus. For this purpose, 120 fishes were used as experimental samples and exposed to 0.1, 0.2 and 0.5 mg/L of Cu nanoparticles for 21 days, and 30 fishes assumed as the experiment control. The mean water temperature of the aquaria was 22±2 ºC, dissolved oxygen 5.2 mg/L, pH at 7±0.004 and the concentration of calcium carbonate was 270 ppm. On 7, 14 and 21 days after exposing the fishes to copper nanoparticles, three fishes were randomly selected from each aquaria, sacrificed and samples from their gill, liver and kidney were taken and fixed in cold 10 % buffered formalin. Then microscopic sections were prepared and examined by light microscope which showed histological alternations in the gill, liver and kidney tissues. Evaluation of these changes could be useful in estimating the harmful effects of copper nanoparticles. Histological alternation in gills included: hyperplasia, fusion and detachment of secondary lamellae, blood congestion in vascular axis of primary filaments, reduced secondary lamellae length and cellular degeneration. Histological changes in liver included blood congestion in the central veins, cytoplasmic vacuolation of the hepatocytes, cellular degeneration and congestion in the blood sinusoids and necrosis of the hepatocytes. Histological changes in kidneys included glomerular shrinkage, severe degeneration in the tubules cells, interstitial tissue and glomerulus, increase in interstitial tissue cells and macrophages aggregation. The degree of damages was more intensive at higher copper nanoparticles concentrations. The result of the study showed that copper nanoparticles could cause severe damages in the vital tissues of Caspian roach; Rutillus rutillus caspicus and have lethal effects for fish.